Coalbed methane diffusion and water blocking effects investigated by mesoscale all-atom molecular dynamic simulations. Issue 68 (17th November 2020) - Zhu, Qingzhong; Lin, Ling; Liu, Zhong; Luo, Yunxiang; Fan, Hongming; Guo, Wei; Zhang, Chen; Wang, Sanshuai; Luo, Wenjia
Abstract : Molecular dynamics simulations of coalbed methane diffusion and water-blocking effects were performed based on mesoscale molecular models. Abstract : In coalbed methane extraction processes, the water blocking effect (WBE) is a formation damage that limits the extraction efficiency. To investigate WBE mechanisms at the molecular level, realistic coal models must be developed to simulate the interplay between methane and liquid phase water in a coal matrix's mesopores and macropores. This study built a massive and highly scalable coal tube model with accurate all-atom force fields. Based on this model, we investigated the adsorption and diffusion of methane and liquid water in the mesopores of coal. We found that methane forms multiple layers of adsorption on the coal surface, and the diffusivity of methane strongly depends on pore sizes and the presence of water. When both methane and liquid water were loaded in the coal tube, the liquid phase formed a nearly impenetrable barrier that prevented methane diffusion. This work provides insights into the mechanism of the WBE and can facilitate further studies on WBE alleviating strategies.